Influence of Ratings and Online Customer Reviews on Purchase Decisions in The Shopee Marketplace - Mubarok, Zaki; Husaini, Fauzan; Prihandayani, Riska Dwi; Qolbi, Tazkiyah Ainul (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, INDONESIA, 2023)
This study aims to examine the effect of customer ratings and reviews on purchase decisions on Shopee. This research used multiple linear regression to estimate the determinants of purchase decision on Shopee. Data was collected through a questionnaire and analyzed to test the relationship between variables. The descriptive verification method aims to describe whether the facts are true or not and explain the relationship between variables by collecting, processing, analyzing and interpreting data in statistical hypothesis testing. The results showed that partially, rating and customer reviews have a positive and significant effect on purchase decisions. At the same time, customer ratings and reviews simultaneously have a positive and significant effect on purchase decisions.